Analysis Health Determinants on the Event of Gestational Hypertension Toward 3rd Trimister Pregnant in Maternity Clinic Budi Asih Turen - Elok Wijayati; Katmini (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
Gestational hypertension is one of the conditions that can arise during pregnancy and can lead to more serious complications. Seizures or eclampsia, brain hemorrhage, pulmonary edema (fluid in the lungs), abrupt kidney failure, and blood clots in the blood vessels are all possible complications of hypertension in pregnancy. This study attempts to determine the factors that influence the risk of gestational hypertension. Weight gain, sleep patterns, and dietary habits are variables that are expected to have a substantial effect on gestational hypertension. The test equipment employed is logistic regression and the study method is descriptive quantitative. The study included 103 pregnant women in their third trimester at Klinik Bersalin Budi Asih, Turen - Malang. The result of this research showed that weight gain received a Sig value of 0.016, which was less than the minimum level of 0.05, indicating that weight gain has a significant effect on gestational hypertension. The sleep patern has a Sig value of 0.006, which is less than the 0.05 threshold, indicating that sleep length has a substantial impact on gestational hypertension. The last variable, dietary habit, has a s Sig value of 0,034, which is higher than the threshold of 0.05, indicating that dietary habit has a significant impact on gestational hypertension. The Chi Square value of 28,678 with a significance level of 0.001 indicates that all of this study's independent variables have a significant influence on gestational hypertension.